Answer:
x+27
Step-by-step explanation:
Let's simplify step-by-step.
4(x+3)+3(5−x)
Distribute:
=(4)(x)+(4)(3)+(3)(5)+(3)(−x)
=4x+12+15+−3x
Combine Like Terms:
=4x+12+15+−3x
=(4x+−3x)+(12+15)
=x+27
Hope you find this Useful!
Answer: 8-a^3
You just simply the expression.
Answer:
Situation 1 is exponential decay. Situation 2 is linear. Situation 3 is exponential growth.
Step-by-step explanation:
Situation 1 is exponential decay because it declined in a non linear way.
600-480=120 480-364=116
Situation 2 is linear because when it declined it has a dependent to another.
400-340=60 340-280=60
Situation 3 is exponential growth because is increases.
To generate the equation we set up the factors
(x+3) * (x-1) * (x-2) which equals
x^2 + 2x -3 * (x-2)
x^3 +2x^2 -3x -2x^2 -4x +6 equals
x^3 -3x -4x +6 which equals
x^3 -7x +6
Answer:
Power of a Quotient.
explanation: The Power of a Quotient Rule states that the power of a quotient is equal to the quotient obtained when the numerator and denominator are each raised to the indicated power separately, before the division is performed.